Bridging the Nanoscopy-Immunology Gap - Shannon, Michael; Owen, Dylan M. (Frontiers in Physics, 2019)
ABSTRACT: Bridging the gap between traditional immunology and nanoscale biophysics has proved more difficult than originally thought whereas for cell biology applications, super-resolution microscopy has already afforded a raft of new concepts. From neuronal segmentation to nuclear pores and the 3D structure of focal adhesions – nanoscopy has begun to illuminate the link between nanoscale organization and function. In the field of immunology, the explanation must typically go further, linking nanoscale biophysical phenomena to the manifestation of specific diseases, or the altered activity of specific immune cell subtypes in a bodily compartment. What follows is a summary of how nanoscopy has elucidated immunological function, and what might be achieved in the future to link quantifiable, nanoscale, biophysical phenomena with cell and tissue functionality. We explore where the gaps in our understanding are, and how they might be narrowed by microscopists, biophysicists and immunologists working together.